2018
DOI: 10.1002/aocs.12171
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Low‐Density and Free‐Flowing Hollow Microparticles from Butter and Fractionated Palm Oil Mixture

Abstract: The use of solid fats is challenging due to difficulty in incorporating into foods, handling during industrial food production, and relatively high-calorie contributions. The objective of this study was to form free-flowing and low-density hollow microparticles from nonhydrogenated fats, namely, butter and fractionated palm oil, using a novel method based on atomization of a carbon dioxide (CO 2 )expanded lipid mixture. The melting point of the fractionated palm oil decreased from 66.2 to 47.3 C above 120 bar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Sousa et al, 2007;Lubary et al, 2011;Mandžuka and Knez, 2008), Gas Assisted Melting Atomization (GAMA) (Bertucco et al, 2007), and atomization of CO2-expanded lipids (Yang and Ciftci, 2016a, b;Yang and Ciftci, 2017;Gudeman et al, 2018) have been reported to form lipid particles. Those methods have been used to form free-flowing powder hollow solid microparticles of palm oil and butter (Gudeman et al, 2018), essential oil-loaded hollow solid lipid micro-and nanoparticles as natural food antimicrobials (Yang and Ciftci, 2016b), free-flowing fish oil-loaded hollow solid lipid micro-and nanoparticles (Yang and Ciftci, 2017), tristearin and tripalmitin microparticles (Bertucco et al, 2007), monostearin microparticles (de Sousa et al, 2007;Mandžuka and Knez, 2008), and milk fat microparticles (Lubary et al, 2011). In those processes, SC-CO2 plays a key role to create a clean and milder environment to protect heat sensitive bioactives, such as omega-3 fatty acids and essential oils, from degradation and oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Sousa et al, 2007;Lubary et al, 2011;Mandžuka and Knez, 2008), Gas Assisted Melting Atomization (GAMA) (Bertucco et al, 2007), and atomization of CO2-expanded lipids (Yang and Ciftci, 2016a, b;Yang and Ciftci, 2017;Gudeman et al, 2018) have been reported to form lipid particles. Those methods have been used to form free-flowing powder hollow solid microparticles of palm oil and butter (Gudeman et al, 2018), essential oil-loaded hollow solid lipid micro-and nanoparticles as natural food antimicrobials (Yang and Ciftci, 2016b), free-flowing fish oil-loaded hollow solid lipid micro-and nanoparticles (Yang and Ciftci, 2017), tristearin and tripalmitin microparticles (Bertucco et al, 2007), monostearin microparticles (de Sousa et al, 2007;Mandžuka and Knez, 2008), and milk fat microparticles (Lubary et al, 2011). In those processes, SC-CO2 plays a key role to create a clean and milder environment to protect heat sensitive bioactives, such as omega-3 fatty acids and essential oils, from degradation and oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Melting points of CLW and CW in SC‐CO 2 were measured in a home‐made SC‐CO 2 phase behavior system according to Yang & Ciftci, 2020 and Gudeman et al (2019) with minor modifications. The vessel composed of two sapphire windows, a microscope, and a camera.…”
Section: Methodsmentioning
confidence: 99%
“…Bulk density ( β ) of the particles was determined using the tap method (Gudeman et al, 2019). Samples were filled into a 25 mL graduated cylinder and tapped slightly to avoid excess air between the particles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations